FUNCTIONAL-SEMANTIC ANALYSIS OF ENCOURAGING MODALITY - Харченко, C. B. (Proceedings of National Aviation University (archive), 2021)
It is devoted to the coverage of issues related to the functional-semantic analysis of the category of motivational modality. It is shown that the qualification and classification of invariants of speech realization of the motivational meaning, which is allocated within the objective modal values, should be carried out taking into account verbal and nonverbal factors. Orientation of motivation for a positive result presupposes both obligatory consideration of known or presumed background knowledge, social and communicative status of communicators, speech situation.